Association between breast nodules, anxiety, depression and metabolic risk factors in a Chinese cohort - Long, Yan; Zhang, Wei; Zheng, Maolan; Xie, Qian; Liu, He; Hu, Xiaotong; Zhang, Xuelan; Huang, Wei; Gao, Xia; Jiang, Chunmao; Jiang, Can; Gao, Dong; et al. (Frontiers in Psychiatry, 2023)
Background: The relationship between anxiety, depression, and metabolic parameters and the incidence of breast nodules is unclear. This study aims to investigate the association between female breast nodules and anxiety, depression and metabolic factors. Methods: This cross-sectional study recruited 390 patients with breast nodules and 467 patients without breast nodules from our center of Health Management from April 2021 to February 2022. Self-rating anxiety scale (SAS) and self-rating depression scale (SDS) were used to assess the level of anxiety and depression. Result: The positive rate of breast nodules in women aged 40 to 49 years old was significantly higher than that of other age women (χ2 =35.533, p＜0.001). Breast nodules in postmenopausal women were significantly lower than those in premenopausal women (26.4% vs 73.6%, χ2 =4.93, p=0.026).The SAS scores of women with breast nodules were higher than those of the no-nodules group (40.99±8.45 VS 38.94±6.89，p＜0.001), same as the SDS scores(41.97±10.33 VS 38.91±7.60, p＜0.001). The number of women suffering from anxiety in the group of breast nodules was significantly higher than that in control (13.8% vs. 4.5%, p＜0.001), and the number of depression in the group of breast nodules was also significantly higher than that in control (14.4% vs. 4.5%, p＜0.001). Women with breast nodules showed a slightly lower UA level compared with subjects without breast nodules (290.11±65.32 vs. 301.43±65.93umol/L, p =0.016). Anxiety and depression status, uric acid, age and menopausal status are significantly associated with the presence of breast nodules. Conclusion: Our findings offer insight into the occurrence of depression and anxiety in breast nodules of Chinese women. Anxiety and depression status, uric acid, age and menopausal status may be the independent risk factors for the occurrence of breast nodules.